Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/ajplung.00133.2014
|View full text |Cite|
|
Sign up to set email alerts
|

Inspiratory resistive breathing induces MMP-9 and MMP-12 expression in the lung

Abstract: Inspiratory resistive breathing (IRB) is characterized by large negative intrathoracic pressures and was shown to induce pulmonary inflammation in previously healthy rats. Matrix metalloproteinases (MMP)-9 and -12 are induced by inflammation and mechanical stress in the lung. We hypothesized that IRB induces MMP-9 and -12 in the lung. Anesthetized, tracheostomized rats breathed spontaneously through a two-way valve, connected to an inspiratory resistance, with the tidal inspiratory tracheal pressure set at 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…In Mycobacterium marinum infection of zebrafish, studied as a model for human tuberculosis, MMP-9 has been shown to be required for granuloma formation (40). MMP-9 and MMP-12 cooperate in tissue remodeling in the lung (41) and may coregulate, as MMP-12 upregulated MMP-9 expression in the presence of IL-1β (42). In the gene networks in T-lep lesions, MMP9 and MMP12 were connected by the common gene ontology terms: "chemotaxis" and "tissue remodeling".…”
Section: Discussionmentioning
confidence: 99%
“…In Mycobacterium marinum infection of zebrafish, studied as a model for human tuberculosis, MMP-9 has been shown to be required for granuloma formation (40). MMP-9 and MMP-12 cooperate in tissue remodeling in the lung (41) and may coregulate, as MMP-12 upregulated MMP-9 expression in the presence of IL-1β (42). In the gene networks in T-lep lesions, MMP9 and MMP12 were connected by the common gene ontology terms: "chemotaxis" and "tissue remodeling".…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to decipher the effects of mechanical stressor (increased inspiratory airway resistance) from the effects of the underlying airway inflammation which is observed in COPD. A series of studies have been performed by adding an inspiratory resistance, so that the tidal pressure during inspiration is set at 50% of maximum ( P i / P i,max =0.5) 9 , 10 . The major findings of these studies are that in a healthy rat lung, inspiratory resistive breathing increases the permeability of the alveolar-capillary membrane of the lung, deranges the respiratory system mechanics, shifting the pressure–volume curve to the right and downward (ie, making the lung less distensible), induces lung inflammation, activates matrix metalloproteinases, and results in acute lung injury and respiratory failure ( Figure 1 ).…”
Section: Effect Of Inspiratory Resistive Breathing On the Lungmentioning
confidence: 99%
“…However, another study demonstrated that MMP-9 was upregulated in a mouse model of DNFB-induced atopic dermatitis, and the IL-31 and T-bet gene were also expressed in the ear epidermis (34). MMP-2 and -12 have been shown to be upregulated in the lung by inspiratory resistive breathing (35). Another study demonstrated that the mRNA levels of MMP-1, MMP-7, MMP-10, MMP-14 and MMP-19 were increased independently of COX-2 in monocytes stimulated with LPS (36).…”
Section: Resultsmentioning
confidence: 99%